Human NCF190H Variant Promotes IL-23/IL-17-Dependent Mannan-Induced Psoriasis and Psoriatic Arthritis - Yanpeng Li; Zhilei Li; Kutty Selva Nandakumar; Rikard Holmdahl (MDPI AG, 2023)
Recently, a major single nucleotide variant on the NCF1 gene, leading to an amino acid replacement from arginine to histidine at position 90 (NCF1R90H), associated with low production of reactive oxygen species (ROS), was found to be causative for several autoimmune diseases. Psoriasis in the skin (PsO) and psoriatic arthritis (PsA) were induced with mannan by intraperitoneal injection or epicutaneous application, evaluated by visual and histology scoring. Immunostaining was used to identify macrophages, NCF1, and keratinocytes. The population of immune cells was quantified by flow cytometry, gene expression was analyzed by RT-qPCR, and the JAK/STAT signaling pathway was investigated by immunohistochemical staining and western blot. We found that the low ROS responder NCF190H variant promotes PsO and PsA (the MIP model). The NCF190H-expressing mice had hyperactivated macrophages, expanded keratinocytes, and dramatically increased numbers of γδT17 cells with upregulated IL-17A, IL-23, and TNF-α. In addition, the JAK1/STAT3 signaling pathway was also upregulated in cells in the psoriatic skin tissues of Ncf190H mice. To summarize, a defined SNP (NCF1-339, also named NCF190H) was found to activate the IL-23/IL-17 axis and JAK-STAT signaling pathways, leading to hyperactivation of macrophages and keratinocytes and causing mouse psoriasis and psoriatic arthritis.